Biomaterials for Bone Tissue Engineering: Properties and Applications - Zaroog O.S.; Satgunam M.; Wei L.C. (Elsevier, 2023)
Tissue engineering is one of few emerging fields that focus solely on developing alternative treatment for tissue and organ repair. It is a multidisciplinary field that uses a combination of cells, engineering materials and suitable biochemical factors to enhance or replace biological function to produce a better clinical procedure to repair damaged tissues and organs. Biomaterials are incredibly significant in tissue engineering in various ways such as; acting as a substrate so that cell populations can attach and migrate, as a cell delivery vehicle, 3-D implant with a combination of specific cell types, to activate specific cellular function in the localized region as a drug carrier, to define the shape of regenerating tissue as a mechanical structure, and to provide space as a barrier membrane for tissue regeneration along with prevention of fibroblast ingrowth into the space. Hence with all the facts in mind, this paper is to do a thorough study and review on the specific research on the biomaterials applications and properties for bone tissue engineering which hopefully could discover a more suitable and affordable biomaterial which can substitutes and represent the future of new therapeutic approaches specifically aimed at clinical applications. 2021 Elsevier Ltd. All rights reserved.